La autoestima en el rendimiento escolar de los niños y niñas con discapacidad visual internos en el instituto Byron Eguiguren de la ciudad de Loja. Durante el periodo marzo a septiembre del 2013 - Pesantez Mendoza, Ana Lucia (2014)
This thesis entitled: SELF-ESTEEM IN SCHOOL PERFORMANCE OF CHILDREN WITH VISUAL DISABILITIES INSTITUTE INMATES IN BYRON CITY EGUIGUREN Loja. DURING MARCH- SEPTEMBER 2013. The overall objective is: Knowing how self-esteem affects school performance of children with visual impairment in internal school Eguiguren Byron City of Loja. The main methods used for this investigation were: scientific, analytic-synthetic, descriptive statistical method. The techniques and instruments used were the survey to teachers, the report notes, and the use of a psychological reagent; self-esteem scale Lucy Reidl. The research sample consisted of 8 classroom teachers, and 14 hospitalized children, leaving a total sample of 22 people surveyed. Upon completion of the present study concluded that children investigated mostly have a low level of self-esteem and school performance level , finding relationship between the two variables ; and that the results found in the research; while the lower the level of self-esteem, achievement levels also low in students. That is why the development and implementation of a proposed intervention which is linked to children / as , parents and teachers of the institution, to upgrade and improve the existing low self-esteem in children / disabled as suggested visual inmates to improve their school performance and their personal welfare.